The benefits and challenges of integrating literary texts in English language textbooks in ethiopian grade 12 English language classrooms - Tamirat Taye (Social Sciences and Humanities Open)
Literary texts are significant in language classrooms because they offer engaging narratives, diverse cultural perspectives, and nuanced expression. This descriptive study assessed the benefits and challenges of integrating literary texts in English language textbooks in Ethiopian Grade 12 English language classrooms. It focused on 240 grade 12 students at three secondary schools in Southwest Ethiopia, who were selected through simple random sampling. The researcher employed questionnaires, interviews, and classroom observations to collect data from the students and English teachers. Statistical analysis was used for quantitative data, whereas teachers' interviews and classroom observations were analyzed qualitatively. The findings revealed that the students recognized the significant benefits of literary texts, including improvements in language skills, critical thinking, and cultural awareness. Yet, they faced noteworthy challenges such as difficulties in vocabulary recognition and comprehension, unfamiliarity with complex language structures, and difficulty in selecting reading texts that align with their interest and relevant themes. In light of these results, suggestions were made to assist students bridge this gap. Suggestions included integrating interactive discussions and activities that connect literary themes to real-world contexts, providing support for language comprehension, and fostering a classroom environment that encourages critical thinking.